(untitled) (Bangladesh Journal of Medicine, 2016)
Introduction:Hypertension is progressively becoming more prevalent in Nigeria. The purpose of the study was to assess the risk factors and occurrence of hypertension among Fulani herdsmen in Nigeria. Methodology:A descriptive longitudinal study on hypertension was conducted among Fulani herdsmen residing in rural communities of Ilorin East and Moro Local Government Areas (LGAs) of Nigeria, from the age of 18 years and above. Eight hundred and seventytwo (872) consenting subjects completed a standardized questionnaire. Blood pressure, weight and height were measured and recorded using standard calibrated equipment. Results:Of the 872 herdsmen, 351 (40.3%) were aged 1830 years and 632 (72.5%) migrated from the NorthWest zone of Nigeria. Almost all (n=858, 98.4%) of the subjects were ignorant of hypertension. Overweight and obesity were uncommon among the subjects. The occurrence of hypertension was 17.3% with overall average systolic blood pressure (BP) of 128.8±12.3 mmHg and diastolic BP of 84.0±8.0 mmHg. Risk factors of hypertension were types of diet [OR 0.578; 95% confidence interval (CI) 0.11311.418, p< 0.028], smoking habit [OR 5.147; CI: 1.02325.884, p < 0.017] and age [OR 2.656; CI: 0.6828.556, p < 0.031]. Conclusion: Majority of hypertensive herdsmen were not aware of their status, signifying a high incidence of undiagnosed and un-controlled BP among these subjects. Public health awareness on the risk factors of hypertension is essential to reduce the burden among this population. Further research is also necessary to measure the trends of hypertension among this population Bangladesh J Medicine Jul 2016; 27(2) : 48-54